Polymer mixed membrane with microflower TiO2 as additive for photocatalyst in organic compound - Ahmad, Raja Adibah; Harun, Zawati; Azhar, Faiz Hafeez; Hussin, Rosniza; Mohd Zin, Mohamad Faiz; Sazali, Norsuhailizah; Syamsul Bahri, Syamsutajri; Jamaluddin, Mohd Riduan; Misdan, Nurasyikin; Kamdi, Zakiah; Hairom, Nur Hanis Hayati (Elsevier, 2021)
This study investigate the performance and physical properties of polymer mixed membrane integrated with the microflower of titanium dioxide (TiO2) that synthesized at different temperature value. Microflower TiO2 has been prepared by hydrothermal method with variation of synthesized temperature at 120 C, 150 C and 180 C and the polymer flat sheet membranes were fabricated via phase inversion technique. In this present work, TiO2 was used as photocatalytic, antifouling and hydrophilicity improvement. Synthesized microflower TiO2 via hydrothermal method offer higher surface area that able to speed up any chemical reaction of TiO2. Prior to the fabrication of polymer mixed matric membrane, the characterization of TiO2 have been conducted to determine the optimum synthesize temperature. Then this was followed by the measurement of properties and performance of the polymer mixed matric membrane. Further observation on the self-cleaning test at different concentration of TiO2 wt (%) of the membranes were conducted. The results obtained showed that membrane at temperature of 150 C with 2.5% of TiO2 wt (%) shows a better result than others with the highest rejection rate of 99.43% that probably due to small finger like structure. Meanwhile for self- cleaning test, membrane with synthesized temperature of 150 C showed a better result than others with the highest of retention rate before and after being exposed to UV light which were 99.42% and 98.66% respectively. Humic acid flux recovery ratio (FRR) showed a better performance for membrane at synthesized temperature of 120 C that may relate to the effect of higher surface area that TiO2 that able to attract more water. As conclusion, PSf/TiO2 membrane at synthesized temperature of 150 C with 2.5% of TiO2 wt (%) shows an excellent result that possessed a strong hydrophilic property by lowering the fouling effect and give higher retention value. 2020 Elsevier Ltd. All rights reserved